Nanotechnological applications in dermocosmetics - Rojas Salas, María Fernanda (2023)
Objective: Identify the types of nanoparticles used in dermocosmetics and their main applications. Methods: A bibliographic review was carried out in the databases Google Scholar, and PubMed, as well as databases subscribed to the system of libraries, documents, and information of the Universidad de Costa Rica such as ScienceDirect, Elsevier, EBSCO, MEDLINE, Clinical-Key, among others. The search was conducted in both English and Spanish.Conclusion: Nanotechnology in the cosmetic industry has been an area that has grown exponentially in recent years. Various types of nanoparticles are used in different skincare applications in the cosmetics industry;however,much research remains to be done on the safety and toxicity of their use for humans and the environment.